2017
DOI: 10.12973/ejmste/80817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hands-on Activities on Conservation, Disgust and Knowledge of Woodlice

Abstract: Although hands-on activities significantly improve achievement and attitudes toward animals, the use of the aesthetically unpleasant is questionable. We investigated whether the use of woodlouse, as an example of an unpopular animal, alters children's conservation attitudes, disgust for and knowledge of woodlice. The experimental group (n = 116), but not the control group (n = 110), achieved a better woodlouse conservation score with hands-on activities, but the intentions for woodlouse conservation were not g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…This also can be attributed, for example, to the novel environment (novel field trip phenomenon Falk et al, 1978). In general, both practical work conditions (in school and out-of-school) decreased the disgust significantly when compared to the control group This is in contrast to another study on disgust reduction through practical work with live woodlice which found no effect (Fančovičová and Prokop, 2017). Thus, we can conclude that the intervention based on workstations with live invertebrates is applicable both, in the school setting and out of school.…”
Section: Discussionmentioning
confidence: 67%
“…This also can be attributed, for example, to the novel environment (novel field trip phenomenon Falk et al, 1978). In general, both practical work conditions (in school and out-of-school) decreased the disgust significantly when compared to the control group This is in contrast to another study on disgust reduction through practical work with live woodlice which found no effect (Fančovičová and Prokop, 2017). Thus, we can conclude that the intervention based on workstations with live invertebrates is applicable both, in the school setting and out of school.…”
Section: Discussionmentioning
confidence: 67%
“…Palmberg et al, 2019;Staatsinstitut für Schulqualität und Bildungsforschung, 2017). Teaching biodiversity at school is not only an obligatory necessity but offers many possibilities for hands-on activities (Fančovičová & Prokop, 2017) or outdoor experiences (Lindemann-Matthies, 2006) to motivate pupils and enrich biology lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Children in preschool and primary school age are an important target group, because young children are particularly interested in living organisms, and like hands-on activities and the investigation of plants and animals outside the classroom (Lindemann-Matthies, 2006). Hands-on activities with invertebrates, for instance, were found to decrease disgust in children and to increase positive emotions towards this group of animals (Fančovičová et al, 2018;Prokop & Fančovičová, 2017). Moreover, studies on significant life experiences of active and informed conservationists have shown that time in nature during childhood is the most frequent reason for their concern and commitment (e.g.…”
Section: Introductionmentioning
confidence: 99%